Plyometric Exercises and Concentration Levels on the Swim-Start Jump of Female Athletes in Metro Lampung (Journal of Physical Education and Sports, 2019)
This study aimed at finding out the difference in the influence of the plyometric jump to box and plyometric barrier hops training on start jump of swimming grab-start, finding out the difference in the influence between groups having high concentration level and groups having low concentration level on start jump of swimming grab-start, and analyzing interaction of plyometric training and the level of concentration on start jump of swimming grab-start. This was a kind of experimental research that used a quantitative descriptive method with a 2x2 factorial design. Additionally, it used the Statistical Product and Service Solution (SPSS) program to calculate the data. The results of the study revealed that there were differences in influence between groups using the plyometric jump to box training method with an average value of 2.623 and plyometric barrier hops training with the average value of 2.581, so that it resulted in the difference with the average value by 0.042, there were differences in influence between athletes who have a high concentration level with an average value of 2.629 and athletes who have a low concentration level with an average value of 2.575, so that it resulted in the difference with the average value by 0.054, and there was the interaction between groups using plyometric training method and concentration levels on start jump of swimming grab-start.